An overview of graphene materials: properties, applications and toxicity on aquatic environments - De Marchi, Lucia (2020)
Due to unique chemical and physical properties, nanomaterials from the Graphene family are being increasingly introduced in all fields of science. The specific roles they can occupy within different applications are attracting increased attention by several industrial sectors. These carbon nanoparticles are released into the environment especially accumulating in aquatic systems. Since the discovery of graphene, a number of research actives are being conducted to find out the toxic potential of the Graphene family materials to different organism's models. Although their toxicity effects are well described for biomedical applications, few data were produced with the specific aim of assessing the toxic effects of these carbon nanomaterials in the aquatic environment. The purpose of this review is to compile up-to-date information on properties, applications and characterization methods of graphene family materials in aquatic environments and identified biological toxic impacts of these NMs, with special focus on graphene oxide based on the most recent literature.